EMPLOYABILITY IN THE ACCOUNTING PROFESSION DURING COVID-19 IN MALAYSIA: A COMPARATIVE STUDY - Dr Meenah a/p Ramasamy; Dr Zam Zuriyati Mohamad; Dr Yamuna Rani a/p Palanimally; Puan Nur Diyana Binti Ismail; Cik Nur Hazrini binti Mohd Zahari (Journal of Islamic, Social, Economics and Development, 2024)
The COVID-19 pandemic has significantly impacted the global economy, leading to widespread unemployment and job insecurity in various industries. This research focuses on the employability of accounting professionals in Malaysia during the COVID-19 pandemic. The study aims to investigate the challenges faced by accounting professionals in finding employment, explore the strategies adopted to enhance employability, and analyze the impact of the pandemic on the accounting profession. The research adopts a comparative methodology, analyzing data from both primary and secondary sources. The findings will contribute to a better understanding of the employability scenario among accounting professionals in Malaysia during the COVID-19 crisis.